2021
DOI: 10.3390/jcm10215115
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Events, Sleep Apnoea, and Pulmonary Hypertension in Primary Sjögren’s Syndrome: Data from the French Health Insurance Database

Abstract: Primary Sjögren’s syndrome (pSS) is an autoimmune disease, associated with a high risk of lymphoma. Mounting evidence suggests that cardiovascular morbidity and mortality are higher in patients with pSS, although data are heterogeneous. The aim of this study was to assess whether pSS patients are at higher risk of hospitalisation for cardiovascular events (CVEs), venous thromboembolic events (VTEs), pulmonary hypertension (PH), and sleep apnoea syndrome (SAS). Through a nationwide population-based retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Excluding these patients meant that the control group presented a disease severity level more comparable to the pSS patients. This cohort has been described in previous studies [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Excluding these patients meant that the control group presented a disease severity level more comparable to the pSS patients. This cohort has been described in previous studies [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Overall, PH is encountered in less than 5% of patients affected by SS ( 70 ). Even so, a recent study revealed that patients with pSS have a higher incidence of hospitalisation related to PH, compared to the general population (aHR = 3.32) ( 91 ). Pulmonary arterial hypertension (PAH) is also considered a rare complication in patients with pSS ( 69 ).…”
Section: Cardiovascular Involvement In Sjogren’s Syndromementioning
confidence: 99%
“…It is known that obstructive sleep apnea (OSA) can induce pulmonary hypertension through hypoxia, as well as contributing to the cardiovascular risk of the individual. A recent study highlighted that hospitalized patients with pSS have a significantly higher incidence of OSA, independently of obesity (AHR= 1.97, [95% CI 1.70- 2.28]; P< 0.001) ( 91 ).…”
Section: Cardiovascular Involvement In Sjogren’s Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Patients may additionally experience a diversity of extraglandular disease manifestations which can cause substantial morbidity (10). Patients with pSS appear to exhibit accelerated (subclinical) atherosclerosis and other cardiovascular risk factors, which is also seen in other autoimmune rheumatic diseases, including systemic lupus erythematosus (SLE) (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%